Extending the investment development path model to include the human environment factor - Zhu, Cherrie Jiuhua; Thomson, Stanley Bruce; Hutchings, Kate; Cieri, Helen De (My University, 2011)
This article aims to address Dunning's call to include the 'human environment' (HE) as a new trend and trajectory for research in international business (IB). Dunning argues that the most important driver for economic advancement is knowledge, which arises from the HE. We extend Dunning's IB theory of the five stages of a country's investment development path (IDP) to include the HE factor. Further, we use China as an example in which to examine the role of human resource management (HRM). We identify and analyze an important link between foreign direct investment, multinational enterprises, and both domestic and global HRM.
Keywords: personnel management; economic development; investments; international business enterprises